PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA PURI SARON HOTEL SEMINYAK KUTA - I Ketut Budiasa; I Putu Bagus Suthanaya (Journal of Tourism and Interdiciplinary Studies, 2021)
This research aims to identify customer perception based on service quality. Service quality is built on a comparison of two main factors, namely customer perceptions of the service they actually receive with the service that is actually expected. If the reality is more than what consumers expect, the service from a company can be said to be of high quality and ideal. This is also what Puri Saron Hotel Seminyak Kuta does in its implementation, excellent service from various aspects is provided by the hotel optimally in order to provide satisfaction and create a good perception of this hotel so that hotel guests have high loyalty. This study formulates the problem of how much influence tangible, reliability, responsiveness, responsiveness, empathy have on customer satisfaction at Puri Saron Hotel Seminyak Kuta. To determine the research sample size from the population. The formula 15 or 20 times the independent variable Azwar can be used. 2008, so the following results will be obtained: 20 x 5 (number of independent variables) = 100. Research results The test results obtained the t value for the physical appearance variable (tangible) showing the t value = 3,430, The test results obtained the t value for the reliability variable (reliability) shows the value of t = 2,318, the test results obtained the t value for the responsiveness variable showing the t value = 2,688, the test results obtained the t value for the assurance variable showing the t value = 3.959, the test The results obtained the t value for the variable caring (empathy) shows the value of t = 2.094 and Testing the effect of the independent variables together on the dependent variable is carried out using the F test. The results of statistical calculations show the calculated F value = 22,183. The research found out that all five dimension of customer service had positive effect to lead costomer satisfaction in Puri Saron Hotel Seminyak.